Pengaruh Penggunaan Kerang sebagai Bahan Pengganti Sebagian Agregat Halus terhadap Kuat Tekan Beton: The Effect of Using Shells as a Partial Replacement Material for Fine Aggregate on the Compressive Strength of Concrete - Lestaluhu, Zahwa Zafira; Leuhery, Lenora; Sahusilawane, Tonny (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
This study aims to analyze the effect of using seashells as a partial replacement for fine aggregates on the compressive strength of concrete and slump value. The research methods include literature review, laboratory experiments following SNI and ASTM standards, mix design calculations, and compressive strength and slump testing on normal concrete samples (BN) and concrete with seashell mixtures (BK). The results indicate that using seashells affects the compressive strength of concrete. Normal concrete achieved a compressive strength of 220.7 Kg/cm², while concrete with a 2.5% seashell mixture achieved a compressive strength of 223.7 Kg/cm², meeting the compressive strength standard for K-200 grade. However, concrete with a 5% seashell mixture only reached a compressive strength of 132.6 Kg/cm², failing to meet the standard for normal concrete. For slump testing, the addition of seashells influenced the slump values. Normal concrete had a slump value of 9 cm, while concrete with 2.5% and 5% seashell mixtures yielded slump values of 8 cm and 10.8 cm, respectively. This study concludes that seashells are effective as a partial replacement for fine aggregates at a 2.5% proportion to improve the compressive strength of concrete, while a 5% proportion does not produce results comparable to normal concrete standards.